(untitled) (Research, Society and Development, 2022)
Introduction: The concept of Palliative Care (PC) has, over the years, undergone updates in its meaning, as well as therapeutic approaches, having been extended to various chronic conditions. The pre-existing model of PC underwent a process of resignification to serve the pediatric population, since it did not fully correspond to the specific needs of this age group. Objective: To characterize children with chronic diseases, eligible for palliative care admitted to a university hospital. Method: A cross-sectional study with a quantitative approach, carried out in a high-complexity public university hospital in southern Brazil. The study population consisted of 101 children aged 0-14 years hospitalized from November 2018 to March 2019. Results: 51.4% of the participants were female, the prevalent age group was 0-5 years old (64.3%). Of the total number of participants, 45 (44.5%) had chronic conditions, and of these, 28 were eligible for PC. However, only 14 (50.0%) received assistance from this perspective. Conclusion: The study identified a significant number of children with chronic conditions and their late insertion in PC when eligible. It was noted the scarcity of national research that addresses PC when aimed at these children.